Radiofrequency resection in oral and oropharyngeal tumor surgery. Issue 1 (February 2020) - Hofauer, Benedikt; Knopf, Andreas; Strassen, Ulrich; Wirth, Markus; Mollenhauer, Martin; Edenharter, Günther; Heiser, Clemens
Abstract: Objective: Various techniques are available for the transoral resection of oral and oropharyngeal tumors. The application of radiofrequency proved successful in the resection of pathologies and achieved a good combination of radicality and hemostasis. The objective of this case series it to evaluate the feasibility of radiofrequency-assisted resection of oral and oropharyngeal tumors. Methods: Patients presenting with oral or oropharyngeal tumors eligible for transoral resection were included. The excision was performed with a 4 MHz microsurgical radiofrequency generator using a monopolar needle. Radiofrequency was evaluated with perioperative (bleeding, tissue sticking, coagulation), objective (wound healing, complications) and subjective postoperative parameters (visual analogue scale of pain, impaired food intake, impaired speak). The surgical specimens were examined regarding entity, width of coagulation margins and the quality of the resection margins and compared to laser-assisted resected specimen. Results: Twenty-five patients were included. 13 patients suffered from benign and 12 patients from malign lesions. Intraoperative bleeding was described as self-limiting in most of the cases and only in some cases the application of additional light pressure was required. Intraoperative tissue sticking was described as none or as resolvable by activation of the radiofrequency generator. Coagulation was limited to the area of resection. No impairment of wound healing or postoperative complications could be observed. Pain, impaired food intake and speak declined steadily. Radiofrequency-assisted resected specimen showed better assessability compared to laser-assisted resected specimen (p < 0.001). Resection margins were predominantly smooth. The width of the coagulation zones was 1593.75 μm on average. Conclusion: Radiofrequency is a suitable tool for the resection of oral and oropharyngeal tumors with a favourable intraoperative performance regarding the peri-incisional bleeding control and a continuous decline of postoperative morbidity.